2009
DOI: 10.1038/nchembio.200
|View full text |Cite
|
Sign up to set email alerts
|

Cell-selective metabolic labeling of proteins

Abstract: Metabolic labeling of proteins with the methionine (1) surrogate azidonorleucine (2) can be targeted exclusively to specified cells through expression of a mutant methionyl-tRNA synthetase (MetRS). In complex cellular mixtures, proteins made in cells that express the mutant synthetase can be tagged with affinity reagents (for detection or enrichment) or fluorescent dyes (for imaging). Proteins made in cells that do not express the mutant synthetase are neither labeled nor detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
162
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(163 citation statements)
references
References 14 publications
1
162
0
Order By: Relevance
“…(Figure 8). 75 Recently, additional MetRS mutant screening strategies have been employed to further improve efficiency and selectivity for NLL. 76 Overall, the simplicity of the expression protocols for incorporating these analogs, as well as practical modified protein yields, make this a 16 suitable method for fluorescent protein labeling either in vitro or in vivo.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…(Figure 8). 75 Recently, additional MetRS mutant screening strategies have been employed to further improve efficiency and selectivity for NLL. 76 Overall, the simplicity of the expression protocols for incorporating these analogs, as well as practical modified protein yields, make this a 16 suitable method for fluorescent protein labeling either in vitro or in vivo.…”
Section: Probing Interactions With Solvatochromic Flaasmentioning
confidence: 99%
“…This strategy has been used to selectively enrich microbial proteins from mixtures of bacterial and mammalian cells. For example, Ngo et al (5) found that proteins made in an E. coli strain outfitted with a mutant MetRS could be labeled with Anl in coculture with murine alveolar macrophages, which were not labeled. Using similar approaches, Grammel et al (6) identified virulence factors from Salmonella typhimurium that were expressed in the course of infection of murine macrophages, and Mahdavi et al (7) profiled Yersinia enterocolitica proteins that were injected into HeLa cells.…”
mentioning
confidence: 99%
“…Using this approach FUNCATwas used to observe protein synthesis in individual dendrites that was diminished on addition of anisomycin, a translation inhibitor, and stimulated on addition of brain-derived neurotropic factor (BDNF), which induces translation-dependent enhancement of synaptic strength (Kang and Schuman 1996). The engineering of a mutant MetRS that is capable of charging the noncanonical amino acid azidonorleucine, which is not recognized by the cell's endogenous MetRS, can be used to restrict the incorporation of azidonorleucine to a defined population of cells (Ngo et al 2009). …”
Section: Fluorescent Noncanonical Amino Acid Tagging (Funcat)mentioning
confidence: 99%